Air Pollution of Nature Reserves near Cities in Russia. (4th June 2020) - Kholodov, Aleksei; Golokhvast, Kirill
Abstract : Today, protected natural areas cover about 15% of the Earth's land. These areas by definition are supposed to be free of pollution; they nevertheless suffer from the effects of aerial transport of anthropogenic polluting substances. In this study, we evaluated the impact of settlements on protected natural areas to determine the optimal distance beyond which the anthropogenic influence would be minimal. For this purpose, we analyzed the particle size distribution and the content of metals in fresh snow samples collected in the Bastak Nature Reserve and the neighboring Birobidzhan city (Russian Federation). Both sites contained comparable proportions of PM10 and contents of heavy metals, which points to the transportation of air pollutants from the city to the reserve. The results of the analysis were summarized and compared with the available data on other nature reserves and nearby populated localities. Based on the research data, pollutant emissions should be decreased for cities that are closer than 50 km to nature reserves. Moreover, authorities should take into consideration atmospheric factors and distance to the nearest settlement when establishing new protected natural areas.